MEASURING THE RELATIVE EFFICIENCY OF THE ACADEMIC DEPARTMENTS OF GOMBE STATE UNIVERSITY USING DATA ENVELOPMENT ANALYSIS (DEA) - MUHAMMAD, A. A; DIKE, I.J (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Data Envelopment Analysis (DEA) has proved to be a suitable technique for assessing efficiency of public institutions because of its unique attribute of incorporating multiple inputs and outputs. Governments at all levels are often faced with difficult challenge of determining the efficiency of the performance of Decision Making Units (DMUs) especially where profit is not a priority. The study applies BCC Output-Oriented DEA model to assess the Relative Efficiency of the Academic Departments in Gombe State University. The inputs are operating expenses, admission rate and academic staff while the outputs are number of graduates produced from each of the department. Data for 2013, 2014, 2016 and 2017 were collected from the Academic Office, Bursary Unit and Establishment Division of the university. Furthermore, multivariable correlation analysis was used to develop a relationship between input and output variables. Results obtained from the analysis indicate that nine (52.94 percent) of the DMUs are efficient while the remaining eight (47.06 percent) are inefficient. Based on that, reference sets were set for those DMUs classified as inefficient. Potential (Target) improvement for each DMU was also set as well as slack analysis. It is recommended that management should review their allocation to DMU2, DMU3, DMU4, DMU11, DMU12, DMU13, DMU14 and DMU15 with a view to improving their efficiencies.